Phenotypic and Genotypic Characterization of Sheep Breeds in Diverse Habitats of Baluchistan Province through the Analysis of the vertnin Gene - Rameez Raja Kaleri,; Hubdar Ali Kaleri,; Ghulfam Ali Mughal,; Ahmed Nawaz Khosa, (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2024)
This study was conducted to identify the vertnin gene in four different sheep breeds of Balochistan by studying their genetic characteristics and analyzing molecular markers. For this purpose, four different sheep breeds, Balochi, Rakhshani, Harnai, and Bibrik, were selected. A total of 10 animals from each breed were chosen to study the impact of breed and the vertnin gene on carcass features. The selection of animals was based on their phenotypic characteristics such as age and teeth. Blood samples of 10 ml were collected and transported to the Laboratory of Molecular Genetics at the Faculty of Veterinary and Animal Sciences, LUAWMS Uthal, Balochistan. Genomic DNA (gDNA) extraction was carried out using a modified inorganic method. The results showed that Balochi had a change in amino acid cytosine (C) > into thymine (T) mutation, Rakhshani had a change in guanine (G) > into adenine (A) mutation, Bibrik had a change in adenine (A) > into cytosine (C) mutation, and Harnai had a change in thymine (T) > into cytosine (C) mutation. The maximum divergence was 0.15715 bp in relation to the comparison in all studied sheep breeds. The phylogenetic results showed that the Balochi breed has 95–97% similarities with the other breeds when sequences were compared. The results revealed that the gel-electrophoresis bands of the Balochi breed were slightly higher, respectively. It was concluded that the vertnin gene exists in different breeds of sheep and might show a broad range of differences, even with similar DNA sequences. However, the purity based on the vertnin gene is at high risk, as a notable difference was found between the Balochi and Harnai sheep.